Layered Double Hydroxide Nanosheets Incorporated Hierarchical Hydrogen Bonding Polymer Networks for Transparent and Fire-Proof Ceramizable Coatings - Bifan Guo; Yimin He; Yongming Chen; Tianci Yang; Chaohua Peng; Weiang Luo; Birong Zeng; Yiting Xu; Lizong Dai (Nano-Micro Letters)
Highlights A transparent and ceramizable coating was developed by incorporating nano-layered double hydroxide nanosheets into hierarchical hydrogen bonding polymer networks. The resulting coating composites demonstrated excellent high-temperature stability and fire resistance, effectively withstanding the direct exposure to a butane flame (~ 1100 °C) in air atmosphere. The mechanisms behind the flame-retardant behavior and ceramicization behaviors were thoroughly investigated and explained.